Gulf aid goes green: reflecting on the geopolitics of environmental sustainability assistance in Arab monarchies - Zumbrägel, Tobias; Sons, Sebastian (Journal of Gulf studies, 2025)
In times of growing decarbonization efforts among the Gulf states, they have started to engage more in green diplomacy and climate action by promoting energy diversification and investing in green developmentalism in the fields of climate mitigation and climate adaptation. In this regard, Gulf aid models are shifting from primarily financial support to technical assistance, with Gulf states increasingly aligning their development aid with global climate commitments. In this transition, Gulf leadership is framing environmental sustainability assistance as a fundamental component of their economic statecraft and diversification strategies, which carry significant geopolitical and geo-economic implications. This article argues that green aid functions as a strategic instrument for bolstering political and diplomatic influence on the global stage, while simultaneously aiding in external power projection efforts.
Online veröffentlicht: 20. Februar 2025